KNOWLEDGE, ATTITUDE, AND PASSWORD PRACTICES: DETERMINANTS OF CYBERSECURITY AWARENESS AMONG STUDENTS IN MALAYSIAN PUBLIC UNIVERSITIES - Cheong, Rayyan Tian Ming; Rahaman, Nur Haffiza; Saidi, Liley Afzani; Wan Yusof , Wan Su Emi Yusnita; Ramlee, Siti Nurhafizah Saleeza (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This conceptual paper explores the determinants of cybersecurity awareness among students at the National Defence University of Malaysia (NDUM), with a focus on three key constructs: cybersecurity knowledge, attitude, and password practices. Cybersecurity threats are increasingly targeting educational institutions, making awareness and secure behavior critical, especially in defense oriented universities. The problem lies in the inconsistent awareness levels across student groups and the lack of a unified approach to address knowledge, behavioral, and attitudinal gaps. This study adopts Protection Motivation Theory (PMT) as the theoretical foundation, integrating threat and coping appraisals to explain students’ motivation for protective behavior. A conceptual model is proposed to examine the relationships among the constructs and their collective influence on cybersecurity awareness. The discussion highlights the theoretical contribution of linking cognitive, affective, and behavioral domains under PMT, and the practical implications for policy and curriculum development at NDUM. The paper concludes by recommending future empirical studies to validate and extend the model for broader application in higher education cybersecurity strategies.